Assessment of the Argentine ant invasion management by means of manual removal of winter nests in mixed cork oak and pine forests - Diaz, Mireia; Abril, Sílvia; Enriquez, Martha L; Gómez, Crisanto (BIOLOGICAL INVASIONS, 2014)
The dynamic in Argentine ant colonies varies seasonally, influenced by biotic and abiotic factors. In winter the spatial range of the colony is contracted in large formations (winter nests) containing a large number of queens and workers. Winter nests are the clue to the species' dispersion power and the invasion of new habitats. For this reason a yearly elimination of queens and workers in winter at the edge (front) of the invasion could be a useful tool for weakening the species' dispersion and therefore limiting its establishment in new areas. Here, we determined the spatial dynamics of the Argentine ant nests during 1 year, and we assessed the invasion management by means of manual removal of winter nests for two consecutive winters, determining its effects during the following 3 years. We mapped nests found in 18 plots divided into two groups: extirpated (with removal of nests) and non-extirpated (control), along the fronts of three locations. Seasonal variation in the abundance of nests and workers, together with the two-year extirpation effects were evaluated. We found that colonies tended to follow an annual cycle of contraction and dispersion, with a decrease in the number of nests as we approached the invasion front. The extirpation was effective only in the front area, where it promoted smaller, less lasting and aggregated nests, as well as a decrease in the abundance of queens and workers. Nests also experienced a decrease during the two first winters but a recovery in the third, when no extirpation was done. Thus, a yearly perturbation should be performed to keep the expansion of the Argentine ant at a low rate, and to limit its establishment in new areas.
Keywords: Argentine ant; extirpation effects; Invasion front; Longterm; Seasonal colony dynamics; Spatial nest distribution

Strength in numbers: large and permanent colonies have higher queen oviposition rates in the invasive Argentine ant (Linepithema humile, Mayr). - Abril, Sílvia; Gómez, Crisanto (Journal of insect physiology, 2014)
Polydomy associated with unicoloniality is a common trait of invasive species. In the invasive Argentine ant, colonies are seasonally polydomous. Most follow a seasonal fission-fussion pattern: they disperse in the spring and summer and aggregate in the fall and winter. However, a small proportion of colonies do not migrate; instead, they inhabit permanent nesting sites. These colonies are large and highly polydomous. The aim of this study was to (1) search for differences in the fecundity of queens between mother colonies (large and permanent) and satellite colonies (small and temporal), (2) determine if queens in mother and satellite colonies have different diets to clarify if colony size influences social organization and queen feeding, and (3) examine if colony location relative to the invasion front results in differences in the queen's diet. Our results indicate that queens from mother nests are more fertile than queens from satellite nests and that colony location does not affect queen oviposition rate. Ovarian dissections suggest that differences in ovarian morphology are not responsible for the higher queen oviposition rate in mother vs. satellite nests, since there were no differences in the number and length of ovarioles in queens from the two types of colonies. In contrast, the higher δ(15)N values of queens from mother nests imply that greater carnivorous source intake accounts for the higher oviposition rates.
Keywords: Colony size; Formicidae; Invasive species; Oviposition rate; Polydomy